A Scarab Feeding on Another Scarab: First Observation of Necrophagy by Canthon histrio (Saint-Fargeau & Audinet-Serville, 1828) on a Dead Passalidae - Dos-Reis, Clemensou; Vaz-de-Mello, Fernando Z.; Delabie, Jacques H. C. (Entomological Communications, 2025)
Besides the widely known behavior of Atta predation by Canthon spp., knowledge of the dietary range of Canthon species is scarce. This note documents the first observation of necrophagy by the dung beetle Canthon histrio on a recently dead Passalidae beetle. The dung beetle exhibited typical nesting behavior by digging into the substrate beneath the Passalidae, although it faced challenges due to the compacted soil. This observation highlights the diverse dietary habits of Canthon species, suggesting that necrophagy may be more widespread than previously documented.